Investigations of Jakšiškis Barrow Cemetery. International Lithuanian–Scandinavian Archaeological research project - Merkevičius, Algimantas (Archaeologia Lituana, 2010)
During the whole period of its existence, the Department of Archaeology at Vilnius University had only a few international archaeological research projects. One of the first international archaeological expeditions took place in 2000, in the barrow cemetery of Jakšiškis (Anykščiai District). It involved representatives from Lithuania and three Scandinavian countries: Sweden, Denmark and Norway. This international project was coordinated by A. Merkevičius, while fieldwork was headed by M. Michelbertas. The aim of this article is to elucidate the reasons which lead to the realization of the project and review the circumstances behind project management.Jakšiškis barrow cemetery first caught the interest of Vidar Berkeland, a Norwegian living close to the place, who discovered that local people referred to this archaeological site as “the Swedish Graves”. In the hope of finding out why the barrow cemetery had this peculiar name and whether it could contain Swedish burials, he addressed the Swedish Embassy in Lithuania as well as other Swedish institutions. This issue incited the interest of Björn Linderfalk, Second Secretary of the Swedish Embassy in Lithuania. As attempts to collect data on the barrow cemetery in Sweden failed, the Archaeology Department of Vilnius University was con-tacted. Associate professor of the Department A. Merkevičius collected data about the barrow cemetery and carried out a survey of the archaeological site. B. Linderfalk and V. Berkeland were told that there are quite many such “Swedish Graves” in Lithuania, but they were usually burials of local residents rather than Swedes. Thus, the probability of finding graves of Swedes at Jakšiškis barrow cemetery was very small. Disappointing as it was, the reply did not stop the desire to investigate the site and reveal who were buried there and when.The organizing committee for the implementation of the project „Investigations of ‘Swedish Graves’ in Central Lithuania“ was set up, comprising B. Linderfalk, Editor of the magazine „Litauen-Nytt“ Jan Krog, diplomats from the Danish Embassy Niels Poulsen and Mette Jensen, Director of the Nordic Information Office Knut Johansen, Swedish Consul in Klaipėda Leif Anermalm, V. Berkeland, Head of the Department of Archaeology of Vilnius University prof. M. Michelbertas and assoc. prof. A. Merkevičius. The organizing committee nominated A. Merkevičius coordinator of the project and M. Michelbertas – head of fieldwork. Various institutions, mostly Scandinavian, were requested to render financial support. Positive replies came from Nordic Information Office, Nordic Embassies, in particular the Swedish Embassy, SAS airlines, such companies as “Genčių nafta“, “Cebeco timber“, “NCC Industry“, and the Cultural Heritage Centre. Besides Vilnius University, Universities of Stockholm, Bergen and Copenhagen were invited to participate. The investigation involved students and postgraduates of the aforementioned universities.From end June to beginning of July 2000 two mounds of Jakšiškis barrow cemetery were investigated under the direction of M. Michelbertas. The first barrow revealed 3 cremation graves, containing female burials, as suggested by grave goods. The second barrow also revealed 3 cremated female graves. These were dated to the 7th or 8th centuries. Investigation of the barrows disclosed that they contained burials of local residents, attributed to the East Lithuanian Barrow Culture group. In the course of investigation, sightseeing trips in the District of Anykščiai were organized.When the investigation at Jakšiškis barrow cemetery were over, sightseeing trips were organized to members of the expedition to Vilnius, Trakai, Kernavė, Kaunas, Klaipėda and Kretinga, including visits to archaeological sites and museums. Members of the expedition not only opened a new page of prehistory, but also learned a lot about the past of Lithuania.